Alternative pathway dysregulation in tissues drives sustained complement activation and predicts outcome across the disease course in COVID‐19. Issue 3 (28th November 2022) - Siggins, Matthew K.; Davies, Kate; Fellows, Rosie; Thwaites, Ryan S.; Baillie, J. Kenneth; Semple, Malcolm G.; Openshaw, Peter J. M.; Zelek, Wioleta M.; Harris, Claire L.; Morgan, B. Paul
Abstract: Complement, a critical defence against pathogens, has been implicated as a driver of pathology in COVID‐19. Complement activation products are detected in plasma and tissues and complement blockade is considered for therapy. To delineate roles of complement in immunopathogenesis, we undertook the largest comprehensive study of complement in COVID‐19 to date, comprehensive profiling of 16 complement biomarkers, including key components, regulators and activation products, in 966 plasma samples from 682 hospitalized COVID‐19 patients collected across the hospitalization period as part of the UK ISARIC4C (International Acute Respiratory and Emerging Infection Consortium) study. Unsupervised clustering of complement biomarkers mapped to disease severity and supervised machine learning identified marker sets in early samples that predicted peak severity. Compared to healthy controls, complement proteins and activation products (Ba, iC3b, terminal complement complex) were significantly altered in COVID‐19 admission samples in all severity groups. Elevated alternative pathway activation markers (Ba and iC3b) and decreased alternative pathway regulator (properdin) in admission samples were associated with more severe disease and risk of death. Levels of most complement biomarkers were reduced in severe disease, consistent with consumption and tissue deposition. Latent class mixed modelling and cumulative incidence analysis identified the trajectory of increase of Ba to be a strong predictor of peak COVID‐19 disease severity and death. The data demonstrate that early‐onset, uncontrolled activation of complement, driven by sustained and progressive amplification through the alternative pathway amplification loop is a ubiquitous feature of COVID‐19, further exacerbated in severe disease. These findings provide novel insights into COVID‐19 immunopathogenesis and inform strategies for therapeutic intervention. Abstract : Complement components, regulators and activation products were measured across the disease time course in severe COVID‐19. Complement dysregulation, particularly involving the alternative pathway amplification loop, was evident across the disease course. Markers of alternative pathway dysregulation were highly predictive of disease course and outcome. The data suggest that drugs targeting the alternative pathway might be of value in severe COVID‐19 and related pathologies.